ANALISIS FAKTOR YANG MEMPENGARUHI KESEHATAN KEUANGAN PERUSAHAAN ASURANSI PRUDENTIAL - Ratam, Aldila Nur Indah Berliana; Azzanina, Nanda; Rivai, Muklas; Selvira, Natalia Aisa; Lase, Marie Vivien; Rohmah, Iffah Nurul; Situmorang, Anita Grace Pretty; Rinaldi, Fanny Dwi Putri; Antika, Siluh Putu Dela; Nadeak, Natasha Putri (Yayasan Nusantara Hasana Berdikari, 2025)
The financial health of an insurance company is a crucial aspect that must be ensured to maintain its ability to manage risks. The insurance industry plays a significant role in economic growth through risk transfer mechanisms. This study aims to analyze the factors influencing the financial health of Prudential Insurance Company during the 2023–2024 period. The method used is factor analysis, a multivariate statistical method designed to identify the underlying structure among financial variables. The analysis results show that two main factors explain 99.2% of the data variance. The first factor is influenced by premium income (X1), claims and benefits paid (X2), and operating expenses (X5). The second factor is influenced by technical reserves (X3) and investment income (X4). These findings highlight the importance of managing premiums, improving operational efficiency, controlling claims, and optimizing assets and investments to maintain the company's financial health. With the right approach, Prudential is expected to maintain its financial stability and competitive position in the insurance industry.